2011
DOI: 10.1186/1758-5996-3-20
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure to cigarette smoke prior to pregnancy in diabetic rats

Abstract: BackgroundThe purpose of this study was to evaluate the effects of cigarette smoke exposure before pregnancy on diabetic rats and their offspring development.MethodsDiabetes was induced by streptozotocin and cigarette smoke exposure was conducted by mainstream smoke generated by a mechanical smoking device and delivered into a chamber. Diabetic female Wistar rats were randomly distributed in four experimental groups (n minimum = 13/group): nondiabetic (ND) and diabetic rats exposed to filtered air (D), diabeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…[12][13][14][15] In contrast, there are no studies evaluating mild diabetes-induced placental effects. Therefore, the aim of this study was at evaluating the effects of oxidative stress status in maternal blood and in the placentas of mild diabetic rats and investigating superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), glutathione reductase (GSH-Rd) activities, and malondialdehyde (MDA) levels at term pregnancy.…”
mentioning
confidence: 99%
“…[12][13][14][15] In contrast, there are no studies evaluating mild diabetes-induced placental effects. Therefore, the aim of this study was at evaluating the effects of oxidative stress status in maternal blood and in the placentas of mild diabetic rats and investigating superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), glutathione reductase (GSH-Rd) activities, and malondialdehyde (MDA) levels at term pregnancy.…”
mentioning
confidence: 99%
“…The morning on which sperm were found in the vaginal smear was designated Gestational Day 0 [6]. The female rats were randomly distributed into two groups (n = 21 rats/group): Control group -fed regular diet; Overnutrition group -fed high caloric diet from day 0 to day 21 …”
Section: Experimental Designmentioning
confidence: 99%
“…GSH-Px activity was expressed in enzymatic activity units per gram of hemoglobin (IU/gHb). For MDA concentration, the absorbance was measured at a wavelength of 535 nm, and the results were expressed as nM of MDA per gram of hemoglobin (nM/g Hb) according protocol of our laboratory [6].…”
Section: Maternal Oxidative Stress Statusmentioning
confidence: 99%
“…In relation the physiological and biochemical changes in the different periods analyzed, it was observed that the rats gained body weight during pregnancy related to fetal and extraembryonic membranes development, according to others studies of our laboratory [18][19][20][21][22] . The blood glucose level in pregnancy and lactation periods was reduced, showing nutrient exchange from mother to offspring as energy source.…”
mentioning
confidence: 99%
“…Then, the increased fetal weight consequently led to maternal weight gain on day 20 pregnancy [18][19][20][21][22] . The progressive increase in triglyceride levels during pregnancy may be related to preparation for lactogenesis and also for the milk production or feeding of offspring.…”
mentioning
confidence: 99%